rd-yttr - Språkbanken Text (University of Gothenburg, 2024)
Utskottens yttranden
Riksdagens öppna data: Yttrande
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik